Could metformin be used in patients with diabetes and advanced chronic kidney disease?. Issue 2 (9th November 2016) - Chowdhury, Tahseen A.; Srirathan, Danushan; Abraham, Georgi; Oei, Elizabeth L.; Fan, Stanley L.; McCafferty, Kieran; Yaqoob, M. Magdi
Abstract : Diabetes is an important cause of end stage renal failure worldwide. As renal impairment progresses, managing hyperglycaemia can prove increasingly challenging, as many medications are contra‐indicated in moderate to severe renal impairment. Whilst evidence for tight glycaemic control reducing progression to renal failure in patients with established renal disease is limited, poor glycaemic control is not desirable, and is likely to lead to progressive complications. Metformin is a first‐line therapy in patients with Type 2 diabetes, as it appears to be effective in reducing diabetes related end points and mortality in overweight patients. Cessation of metformin in patients with progressive renal disease may not only lead to deterioration in glucose control, but also to loss of protection from cardiovascular disease in a cohort of patients at particularly high risk. We advocate the need for further study to determine the role of metformin in patients with severe renal disease (chronic kidney disease stage 4‐5), as well as patients on dialysis, or pre‐/peri‐renal transplantation. We explore possible roles of metformin in these circumstances, and suggest potential key areas for further study.